The International Society for Bipolar Disorders (ISBD) Task Force report on the nomenclature of course and outcome in bipolar disorders. - Tohen, M; Frank, E; Bowden, C; Colom, F; Ghaemi, SN; Yatham, L; Malhi, G; Calabrese, JR; Nolen, W; Vieta, E; Kapczinski, F; Goodwin, G; et al. (2009)
OBJECTIVES: Via an international panel of experts, this paper attempts to document, review, interpret, and propose operational definitions used to describe the course of bipolar disorders for worldwide use, and to disseminate consensus opinion, supported by the existing literature, in order to better predict course and treatment outcomes. METHODS: Under the auspices of the International Society for Bipolar Disorders, a task force was convened to examine, report, discuss, and integrate findings from the scientific literature related to observational and clinical trial studies in order to reach consensus and propose terminology describing course and outcome in bipolar disorders. RESULTS: Consensus opinion was reached regarding the definition of nine terms (response, remission, recovery, relapse, recurrence, subsyndromal states, predominant polarity, switch, and functional outcome) commonly used to describe course and outcomes in bipolar disorders. Further studies are needed to validate the proposed definitions. CONCLUSION: Determination and dissemination of a consensus nomenclature serve as the first step toward producing a validated and standardized system to define course and outcome in bipolar disorders in order to identify predictors of outcome and effects of treatment. The task force acknowledges that there is limited validity to the proposed terms, as for the most part they represent a consensus opinion. These definitions need to be validated in existing databases and in future studies, and the primary goals of the task force are to stimulate research on the validity of proposed concepts and further standardize the technical nomenclature.